LTE uplink scheduling in multiprocessors system - Mahmoud Mahmoud Sayed Hussein (ХНУРЕ, 2020)
The main objective of the thesis is to design a parallel processing algorithm for LTE uplink in a multi processor system. In the thesis evaluate the performance of this algorithm with to throughput, efficiency and as algorithm complexity. The uplink LTE scheduler algorithm can be parallelised efficiently over several digital signal processors in a multi-core environment. Is submitted algorithm are evaluated against each other in terms of throughput, time efficiency.Also, the result is compared with serial scheduling process. To simulated the uplink scheduler algorithm indicates that the parallel scheduling algorithm is able to achieve higher time efficiency than serial scheduling algorithm, while keeping the same throughput performance. The time improvement depends on the number of schedulable UEs in the system, processors number and the throughput trade-off